The effects of glucose addition and water table manipulation on peat quality of drained peatland forests with different management practices - Aaltonen, Heidi; Zhu, Xudan; Khatun, Rikta; Laurén, Annamari (Ari); Palviainen, Marjo; Könönen, Mari; Peltomaa, Elina; Berninger, Frank; Köster, Kajar; Ojala, Anne; Pumpanen, Jukka (Wiley, 2022)
Peatlands are globally significant C storage because waterlogged conditions slow down organic matter (OM) decomposition. Changes in the water table (WT) because of global warming or drainage, consecutive vegetation succession, and enhanced root exudation causing priming may transform peatlands from C sinks to sources. We studied how glucose addition, WT, and forest harvesting affect the chemical composition of peat and decomposition rate by incubating peat columns collected from drained clear-cut (CC) and forested (FD) peatlands. Columns were divided into high or low WT, and half were labeled with 13C to study the priming effect on peat decomposition and peat chemical quality. We measured CO2 fluxes, peat OM, and water quality. There was no detectable priming effect after glucose addition. Lowering of the WT led to increased CO2 efflux, which during the measurements averaged between 39 and 291 μg m–2 s–1. Low WT also decreased the proportion of water-soluble OM in CC areas but not in FD areas. The proportion of recalcitrant OM in surface peat was higher in forest than in clear cut. Forest management also affected the quality of dissolved OM in soil water, with CC showing higher concentrations of recalcitrant compounds. Decomposition and OM quality were governed by forest management practices and WT manipulation. In the future, the C sink capacity of forested peatlands will be regulated by changes in WT level, forest management, and quality of OM.
Keywords: peatland forests; water table; glucose; forest management